Resistive curing of glued-in rods. (25th January 2021) - Ratsch, N.; Burnett-Barking, M.; Böhm, S.; Myslicki, S.; Voß, M.; Adam, M.; Vallée, T.
Graphical abstract: Highlights: Resistive heating is a simple technique to speed-up the curing of glued-in rods. The technique enables bonding of glued-in rods under low temperatures. Glued in rods with epoxies exhibited no loss of strength under low temperatures. Abstract: Adhesive bonding is a joining technique that enjoys increasing popularity in industry, including timber engineering. However, two major shortcomings still delay their widespread use, in particular on-site: long process times, and temperature requirements for curing. Accelerated curing is seen as one way to overcome both. In this paper, resistive heating is investigated as a method to both substantially accelerate curing, and to make it possible even under low temperature. The technique is illustrated on glued-in rods (GiR), a typical adhesively bonded structural joint widely used in timber engineering. Resistive heating was achieved by wrapping a thin Constantan wire within the threads of a rod, which was then subjected to an electrical current. In a series of tests, the performance of three two-component epoxies (2 K-EPX) and one two-component polyurethane (2 K-PUR), all commercially available, were investigated in terms of load capacity after resistive heating under room temperature (RT), +5 °C, and –10 °C. The results indicate that GiR bonded with two of the 2 K-EPX exhibited no significant differences in terms of joint capacity, regardless of the temperature under which they were cured, but that the 2 K-PUR proved very sensitive from departures from the recommendations of the technical data sheet. The results give, in particular practitioners, valuable indications on how to implement resistive heating in real-life applications.